Policy Imperatives for Ascertaining Inclusivity and Equity in ELT An Experimental Study with Indigenous Learners in India - Chandalia , Hemendra Singh (Journal of NELTA, 2025)
This article explores the challenges and pedagogical implications of teaching English to indigenous learners in India, who comprise approximately 8.25 percent of the nation's population. Situated within socio-linguistic and cultural diversity, the study argues that English instruction for these communities is best understood through an English as a Foreign Language (EFL) framework rather than as English as a Second Language (ESL). Emphasising the role of English as a vehicle for social mobility and economic opportunity, the paper highlights the necessity of inclusive English Language Teaching (ELT) policies that account for learners' linguistic and cultural contexts. It critiques prevailing assumptions about Mother Tongue Interference and advocates for the integration of indigenous lexical and syntactic features within English teaching materials. The article proposes pedagogical strategies and text-based interventions aimed at bridging linguistic gaps while acknowledging the learners' native languages as valuable educational resources. These proposed pedagogical strategies aim to contribute to more equitable ELT practices that empower marginalized indigenous learners to use English eff ectively as a means of communication and participation in broader societal domains.